ANALISA PENGENDALIAN KUALITAS STATISTIKA ASAM LEMAK BEBAS PADA PRODUKSI MINYAK KELAPA SAWIT DI PT. SEPANJANG INTI SURYA MULIA - SP., Irianto; Arahman, Emy; Selvianti, Isye; Nurul Adha, Else (Politeknik Negeri Ketapang, 2021)
This study aims to determine whether the parameters of free fatty acids in PT. As long as Intisurya Mulia, the Mulia Oil Mill factory is within quality control limits based on the X-bar and R-bar control chart, looking for factors that affect the value of CPO (Crude Palm Oil) free fatty acid content in production oil, as well as seeking solutions to the problem causes increase in the quality of free fatty acids. The test results using the control chart (control chart) obtained the results of the X-bar and R-bar control chart, on the X-bar control chart there is data that crosses the lower control limit, and the results data outside the upper control limits. The results of the quality of free fatty acids, there are data that are outside the control limits. Whereas the R-bar control limit states that the free fatty acid content in the production oil is still under control, because all data is still within the control limit R and there is no data outside the upper control limit or lower control limit.